A new case of myelodysplastic syndrome associated with t(3;3)(q21;q26) and inv(11)(p15q22). Issue 6 (December 2020) - Monti, Valentina; Bagnoli, Filippo; Bolli, Niccolo'; Vittoria, Laura; Stioui, Sabine; Moiraghi, Maria Luisa; Pruneri, Giancarlo; Testi, Maria Adele
Introduction: Myeloid malignancies are associated with a number of recurrent and sporadic rearrangements that may be oncogenic by ensuring growth advantage and/or increased survival. t(3;3)(q21;q26) has been recognized as a recurrent abnormality in myelodysplastic syndromes (MDS) with poor prognostic significance. Inversion of chr(11) engendering NUP98-DDX10 chimeric product is sporadic and usually associated with diseases with poor prognosis (therapy-related myeloid neoplasm). To date, these cytogenetic abnormalities have been described as isolated events. Case description: We report the first case of an 80-year-old man with high-risk MDS harboring a translocation t(3, 3)(q21q26) jointly with an inv(11)(p15q22) detected by fluorescent in situ hybridization analysis and conventional cytogenetic techniques. Conclusion: A similar pattern of acquisition was never described before in MDS. The coexistence of two independent, high-risk oncogenic, rare events in the same clone suggests that there may be a functional constraint for synergy between the two events, leading to a proliferative advantage and suggests the utility of extended genotyping in myeloid malignancies.